Workshop Menulis Fiksi Autobiografis Dalam Skema Autobiografi Poskolonial Untuk Guru Sekolah Al-Irsyad Satya Islamic School Bandung - Manggong, Lestari; Adipurwawidjana, Ari Jogaiswara; Maulana, Sandya (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2018)
As an international school which is an affiliation of Al-Irsyad Singapore, the curriculum applied at Al-IrsyadSatya Islamic School, Kotabaru Parahyangan, Bandung is Cambridge and national curriculae. Thus, the language usedin the classroom and in school area is English. The combination of the two curriculae causes two cultures (English andIndonesian) to meet.The teaching-learning activities conducted by teachers who were participants of the workshop isbasically the area where the two cultures meet. It is within this frame that postcolonial context becomes necessary as anapproach lens of the writing activity conducted in the workshop within the scheme of Community Engagement. Thisarticle describes the workshop on writing autogiobraphical fiction in the scheme of postcolonial autobiography forteachers of the English Department, Al-Irsyad Satya Islamic School, Kotabaru Parahyangan, Bandung. The participantswere teachers whose daily responsibilities are related to teaching-learning activities in English. This workshop is projectedto assist teachers in having consciousness both within themselves and their surroundings, and also the ability to identifytheir positions in the global world. The main activity of this workshop is writing fiction whose materials related topersonal experiences